PHYSIOTHERAPY MANAGEMENT FOR CERVICAL RADICULOPATHY: A CASE STUDY - Wachidah, Rahayu Noor; Herawati, Isnaini (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Cervical radiculopathy (CR) is a disorder of the peripheral nervous system where the resulting cervical nerve root (CNR) pathology produces chronic pain and disability.11 which is manifested by neurological impairments caused by thightness of neck muscles due to poor postural alignment.13 Cervical radiculopathy(CR) patients demonstrate sensori motor problems radiating along the distribution of a nerve root in the upper limb, multimodal therapeutic program had significant improvement in CR.7,14,21 Case Presentation: A 45-year-old female administration worker presented as direct access to physical therapy with symptoms suggestive of cervical radiculopathy. Her examination revealed strength, tingling sensation, and restriction of rotate her neck to the left side. Following two weeks of conservative treatment, consisting of multimodal intervention, exercise therapy, home program and education. Management and Outcome: A multimodal physical therapy was shown to be effective in reducing pain, functional disability and increasing cervical range of motion in old people with degenerative cervical radiculopathy.22,23 Discussion: In most patients with cervical radiculopathy, nonoperative treatment is effective. In a oneyear cohort study of 26 patients diagnosed with herniated nucleus pulposus and symptomatic radiculopathy, a focused, non-operative treatment program was successful in 92% of patients. Little high- quality evidence supports the use of an individual nonoperative treatment; however, a multimodal approach may lighten symptoms.23,20, Conclusion: Physiotherapy management in the group setting use the two weeks of multimodal intervention and exercise program. The specific technique of multimodal intervention and exercise were used to treat the cervical radiculopathy.23,24,25